The Existences of International Law in The Establishment of Indonesian National Regulation on The Protection of Traditional Knowledge - Budi Hermawan Bangun (Universitas Ahmad Dahlan, 2019)
Introduction to The Problem: The debate about whether the protection of traditional knowledge governed by international law has led developing countries, such as Indonesia, to have the potential for traditional knowledge to feel disadvantaged.Purpose/Objective Study: This paper intends to discuss the existence of international law in the formation of Indonesian national regulations concerning the protection of traditional knowledge.Design/Methodology/Approach: This research designed as doctrinal legal research. The data used in this study are secondary data which analyzed qualitativelyFindings:Â From the results of research and discussion it is known that stipulation of regulations related to the protection of traditional knowledge in Indonesia needs to be accompanied by efforts to encourage the acceptance of national interests in international agreements, both through increasing TRIP agreements and the ASEAN framework. Also, it must be ensured that all binding international legal instruments related to traditional knowledge will truly benefit especially the community of traditional knowledge owners in Indonesia.